Participation and youth in the Teaching of Sociology: contributions of PIBID Social Sciences (Simbiótica. Revista Eletrônica, 2024)
This article examines how the Institutional Teaching Initiation Scholarship Program (Pibid), in the Social Sciences subarea of the Federal University of Espírito Santo, produced impacts on the teaching-learning process and on the political formation of students, in a state high school in Vitória-ES. The analysis of Pibid's contributions considers the innovation in pedagogical practice, in particular the educational project “Student Participation” developed in the Sociology discipline, from 2014 to 2017. This project sought to expand the conditions for student participation from a pedagogical work: enabling the student to be an active agent and builder of knowledge and fostering different forms of political action. The research is based on the case study method: participant observation, interview, survey and analysis of fanzines. The study indicates that the implementation of Pibid contributed to students' cognitive competence in understanding and communicating, impacting their associative profile and perceptions about participation.
Keywords: Participation; Youth; Sociology; Pedagogical practice